ANALISIS TINGKAT BAHAYA EROSI DI SUB DAS BANYUHIRANG DAS MALUKA KOTA BANJARBARU - Rahmadi Rahmadi; Muhammad Ruslan; Syarifuddin Kadir (Universitas Lambung Mangkurat, 2020)
In understanding of climate characteristics in Indonesia in which rainfall is relatively high, and the sun shine is relatively long, combined with the activities of shifting farming and the traditional soil preparation and forest fire in the dry season , the properties of soil and foret land in genral has become worsening. By the action erodibility of rain water and the fragile properties of soil will disturb the hidro=orology of land which will raise the level of erosion hazard (LEH). The condition also causes soil degradation of soil fertility and reduced agriculture production. The objective of research is to analyse the level of erosion hazard (LEH) in the area of sub-watershed of Banyuhirang, watershed of Maluka, Banjarbaru municipality. The research method is the arrangement of data-spatiAl of forest land in terms of land unit combinrd with land cover of forest, plantation, shrub and so on. The calculation leh uses the formula of universal soil loss equation (USLE). The result of research is as follows. For the forest cover of lu-13, lu-24 and lu-15 the leh is I-R whis is relatively small and medium for and IIS for 81,96 ha. For plantation land cover of lu-02 and lu-09, leh is is i-R for 3.417 ha; for plantation land cover of lu-05 and lu-08, leh is leh is II-S for 1.004,,93. Ha. For shrub land cover of lu-lu-01 and lu-04, the leh is III-B for 5.166,17 ha. For shrub land cover of lu-07 and lu-11, the leh is IV SB for 437,73 ha. And finally for the bare land of lu- lu-03, lu-05, lu-07 and lu-10 and lu-12, the leh is IV SB for 1.739,72 ha.Keywords : levelof erosion hazard; land cover